2014
DOI: 10.1021/ac403353x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Isotope Ratio Analysis of Steroids by High-Temperature Liquid Chromatography-Isotope Ratio Mass Spectrometry

Abstract: Generally, compound-specific isotope analysis of steroids is carried out by gas chromatography combined with isotope ratio mass spectrometry. Thus, a derivatization of the steroids prior to the measurement is compulsory, and a correction of the isotopic data is often necessary. To overcome this limitation, we present a new approach of high-temperature liquid chromatography coupled with photodiode array detection and isotope ratio mass spectrometry (HT-LC/PDA/IRMS) for the carbon isotope ratio analysis of uncon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Despite these problems, LC/IRMS has been used to analyze compounds in various sample media, including caffeine in beverages; 13 organic acids, glucose, and fructose in lime and lemon juices; 14,15 glycerol and ethanol in wine; [16][17][18] vanillin in chocolate bars and snack foods; 19 glyphosate and aminomethylphosphonic acid; 20 sulfonamides in pharmaceuticals; 21 glucose in blood plasma; 22 amino acids; 23,24 steroids; 25 and sugars (glucose, fructose, disaccharides, trisaccharides, and oligosaccharides) in honey. [26][27][28][29] Honey is a highly nutritious functional food composed mainly of glucose, fructose, minor sugars, organic acids, amino acids, vitamins, and minerals.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these problems, LC/IRMS has been used to analyze compounds in various sample media, including caffeine in beverages; 13 organic acids, glucose, and fructose in lime and lemon juices; 14,15 glycerol and ethanol in wine; [16][17][18] vanillin in chocolate bars and snack foods; 19 glyphosate and aminomethylphosphonic acid; 20 sulfonamides in pharmaceuticals; 21 glucose in blood plasma; 22 amino acids; 23,24 steroids; 25 and sugars (glucose, fructose, disaccharides, trisaccharides, and oligosaccharides) in honey. [26][27][28][29] Honey is a highly nutritious functional food composed mainly of glucose, fructose, minor sugars, organic acids, amino acids, vitamins, and minerals.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al . demonstrated the utility of LC/IRMS in separating 19‐norandrosterone, T, EpiT, A, E, and 5β‐pregnane‐3α,17α,20α‐triol using high‐temperature LC and determining respective carbon isotope ratios, which might open new possibilities of sports drug testing in the future …”
Section: Anabolic Agentsmentioning
confidence: 99%
“…Zhang et al demonstrated the utility of LC/IRMS in separating 19-norandrosterone, T, EpiT, A, E, and 5β-pregnane-3α,17α,20α-triol using high-temperature LC and determining respective carbon isotope ratios, which might open new possibilities of sports drug testing in the future. [69] Alternative matrices and complementary approaches Detection possibilities concerning AAS in alternative matrices have been assessed with particular attention being paid to testosterone and its esterified derivatives. Since transdermal testosterone applications have been shown to result in only modest alterations of the urinary steroid profile, the option to use oral fluid was tested by Thieme et al [70] Following the transdermal administration of approximately 3-7 mg of testosterone, salivary concentrations of the target analyte increased from baseline (30-142 pg/mg) to more than 1000 pg/mg over a period of 16 h, suggesting a viable means to efficiently screen for the misuse of transdermal testosterone preparations.…”
Section: Confirmatory Testing Procedures -Irms: Complementary Informamentioning
confidence: 99%
“…amino sugars) and sports (e.g. doping; steroids) . A number of these disciplines utilize standard analytical CSIA techniques.…”
mentioning
confidence: 99%
“…Possible fractionation must also be controlled in derivatization for subsequent GC/IRMS measurements. Both EA/IRMS and GC/IRMS CSIA also require additional corrections, which increase the uncertainty of the determined values …”
mentioning
confidence: 99%